APPLICATION OF CASE STUDIES FOR THE FORMATION OF ECOLOGICAL CULTURE IN PROSPECTIVE BIOLOGY TEACHERS - Kamelia Yotovska; Victoria Necheva; Petia Genova-Kalou (Science & Research)

(untitled)
Coping with environmental pollution is a systematic challenge for public actors, economic sectors and education. In this article the methodology for the application of environmental cases in the process of training students - future teachers of biology is developed. Case solving in the learning process is based on the consideration of cases taken from practice or very close to practice that is problematic and/or difficult to solve. The article presents a system of case studies that include primarily eco-innovation, services, and models, new solutions such as advanced household heating technologies, or innovative ways to reduce air pollution from energy use, transport and agriculture. The methods used in this study are theoretical analysis and synthesis, focus groups. The cases developed are two main types: cases where the problem situation is described, no decision has been made and decision-making possibility is discussed and case studies that describe the problem situation, a decision or series of decisions have been made, and the correctness of the approach and the decision has been discussed. Students' opinion on the application of the elaborated case system is that they develop skills to: identify problems and rank them in importance; assess possible solutions and choose a solution based on rational arguments; take a decision in a limited time.